(untitled) (Journal of Bangladesh Academy of Sciences, 2011)
The reaction of thiamine.HCl (ThHCl) with K2Cr2O7 has been studied in aqueous solution at room temperature. The compound obtained is ionic 1 : 1 in which thiamine is present as a cation and Cr2O7 2- as an anion. The chemical formula of the salt, (C12H18N4OS) (Cr2O7) (symbolically ThHCr2O7), has been established by elemental analysis, IR and UV/Vis spectra, magnetic measurement, thermal analysis, conductivity measurement, cyclic voltammetric study and X-ray diffraction analysis. DOI: http://dx.doi.org/10.3329/jbas.v35i1.7970 Journal of Bangladesh Academy of Sciences, Vol.35, No.1, 51-59, 2011